Mirza Muhammad Haidar Dughlat Kurkan - Haidar, Mansura, (Brill | Manohar Publishers & Distributors, 2019)
Although valuable works have been written on the Mughal dynasty throughout the world, Mirza Haidar and his achievements failed to get the attention they rightly deserved perhaps because he was constantly surrounded by a galaxy of luminaries hence the need for this humble corrective endeavour. With his multifarious contribution to the develop‑ ment of Kashmir during the short rule of a decade amidst political problems and internecine warfare, Mirza Haidar Dughlat Kurkan, born in Tashkent, in 1499/1500, proved himself to be a remarkable man of many parts - a gallant general, a good painter, a calligrapher, born poet, excellent administrator and above all a great scholar and historian. Despite extensive patronage to scholars and historians, no official history was compiled and his own magnum opus Tarikh-i Rashidi is far from being a focused court history, memoir, or autobiography. Nevertheless, a man of his calibre was not doomed to be wiped out from pages of history as he had earned enough through his deeds to immortalize his name and fame. There are sufficiently rich accounts and stray references scattered throughout the huge treasure of manuscripts as this volume documents and also enough in his own book about himself and the region of Kashmir. Mirza Haidar's worth as a historian of medieval era, his wealth of cultural legacy which he bequeathed to the posterity, his administrative skills and capabilities with which he regulated and improved administrative affairs in Central Asia and Kashmir and augmented the economic resources, his artistic bent of mind which enriched not only the sphere of fine arts and handicrafts but added considerably to the field of urban development, literature, history and art will never be forgotten.